OPTIMASI SUHU DAN WAKTU EKSTRAKSI ULTRASONIK BUNGA TELANG (Clitoria ternatea) TERHADAP AKTIVITAS ANTIBAKTERI Staphylococcus aureus - Avivah (2023)
Staphylococcus aureus is a common bacterium that causes infection in humans where the antibacterial substances generally used are synthetic antibiotics but many are experiencing resistance. The use of herbal extracts and antibiotics has been proven to overcome bacterial resistance. Butterfly pea flower (Clitoria) turns out to be a natural ingredient that has an antibacterial effect. This research aims to determine the optimal time and temperature for ultrasonic extraction of butterfly pea flowers in producing high levels of flavonoids and phenols to prevent the growth of these bacteria. The research method here applies ultrasonic extraction which has the category of temperature and time to achieve optimal extract as anti-bacterial.The results showed that extraction at 55℃ for 15 minutes produced the highest levels of flavonoids and phenols with a content of 53.51 mg QE/g and 62.82 mg GAE/g In addition, the extract with a concentration of 100% showed strong antibacterial activity against the growth of S. aureus with a yield of 11.69 mm, whereas at a concentration of 20%, it was classified as a weak category which had a slave zone of 2.78 mm. The conclusions of this study were in accordance with the analysis data distribution was normal and homogeneous and for the one way ANOVA H0 test was rejected this indicated that the methanol HCL extract of butterfly pea flowers at 55⁰C for 15 minutes had optimum anti-bacterial activity against S. aureus.